Trinidad and Tobago : Press Release; Financial System Stability Assessment; and Statement by the Executive Director for Trinidad and Tobago. (IMF Staff Country Reports; Country Report, 2020)
The FSAP work was mostly conducted prior to the COVID-19 crisis. Given the FSAP's focus on medium-term challenges and tail risks, its findings and recommendations for strengthening policy and institutional frameworks remain pertinent. As the growth projections were significantly revised downward since the FSAP, the quantitative risk analysis on bank solvency was complemented to include illustrative scenarios to quantify the possible implications of the COVID-19 shock on bank solvency.